ANALISIS PENGUKURAN DAN PENGAKUAN PENDAPATAN PADA PT. BNI SYARIAH CABANG GRESIK - RIZQI MARCELLINA, SASKYA Rizqi (Jurnal Akuntansi AKUNESA, 2013)
This researchis entitled the Confession and Measuring of Income Profit Sharing atPT. BNI Syariah Gresik branch. The objective of this research is to know of how is theconfession and measuring of income profit sharing at PT. BNI Syariah Gresik branch and toknow what is the base for the confession and measuring income profit sharing. The results ofresearch show that the confession and measuring of income profit sharing at PT. BNISyariah Gresik branch has been adjusted with the new PSAK concerning with Mudharabahand Musyarakah Accounting that is PSAK No. 105 and 106 of 2007.Key words:Confession, Measuring, Income and Profit Sharing